Normatywne uwarunkowania procesu wdrażania transformacji energetycznej w Polsce na podstawie polityk energetycznych UE i Polski oraz wobec zagrożeń i wyzwań unijnego wewnętrznego rynku - Marszałek, Marcin (Polityka i Społeczeństwo, 2020)
This work endeavours to define energy policy, comprehended in our times in comparison to threats and challenges to the functioning of the energy sector within the EU internal market. Analysis of the legal of the manifestations (acts) of the national and EU energy policy, the relationships between the national energy policy focused on achieving national targets inside a member state, as well as the energy and climate policy of the EU, its interpretation and considered scenarios of a change indicate only a partial discrepancy of both policies, directions and action strategies defined in them, which are accompanied by implementation instruments. On a domestic basis the objective of the energy policy is to balance the efforts of the players in the energy market to maximise the achieved financial effect with the necessity of the stable functioning and development of energy companies, above all, manufacturers and operators of a system compliant with this policy on the one side and customers expecting low prices, reliability and stability of supplies on the other side. Development of production based on emission-free and low-emission technologies (including renewable energy sources, RES) seems to be a necessity resulting from the EU legislation. In this respect the EU energy policy and the Union political discourse explicitly present a strong commitment to the development of new manufacturing technologies, without any encouragement to restitute or develop technologies not based on RES or cogeneration. The strategic task of the state is to skilfully combine Union tendencies with the Treaty freedom of the state to define use of indigenous sources of primary energy and carefully considered support for the transformation of the national power industry.